PERANAN EKSTRAKURIKULER OLAHRAGA TERHADAP MOTIVASI BELAJAR SISWA DALAM PEMBELAJARAN PENDIDIKAN JASMANI - Hidayat, Yudi; Hambali, Sumbara (STKIP Pasundan, 2019)
The purpose of this study was to determine the role of extracurricular sports activities on students' motivation in physical education at Cimahi City 7 Junior High School. The research method used is the expoct facto method. The research population was students of class VII to IX who were active in the extracurricular activities of futsal, soccer, volleyball, and basketball as many as 40 people with a sample of each extracurricular are 10 people both sons and daughters. The instrument used is a questionnaire. The analysis technique used is percentage. The results of this study indicate that the role of extracurricular sports activities has a very large influence on students' motivation in attending physical education learning which is equal to 86.5% which falls into the very high category.